2016
DOI: 10.1007/s00436-016-4916-6
|View full text |Cite
|
Sign up to set email alerts
|

Henneguya paraensis n. sp. (Myxozoa; Myxosporea), a new gill parasite of the Amazonian fish Cichla temensis (Teleostei: Cichlidae): morphological and molecular aspects

Abstract: The present study describes light microscopy, transmission electron microscopy, and molecular analyses of a myxosporid found parasitizing the gill region of the teleost fish Cichla temensis, collected from the Tocantins River, near Cametá, Pará State, Brazil. The prevalence of infection was 60 %. The spore-containing cysts that were located in the gill lamellae were oval and whitish. The spores had a mean length of 42.3 ± 0.65 μm; fusiform body, 12.8 ± 0.42-μm long and 8.6 ± 0.32-μm wide; each of the two valve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The spore for this study was shown to be larger in relation to those described in Velasco et al (2016) who identified H. paraensis, parasitizing Cichla temensis in the Tocantins river, state of Pará with spores averaging 42.3 ± 0.65 lm of total length, with body measuring 12.8 ± 0.42 lm (12.38-13.22 lm) in length and 8.6 ± 0.32 lm (8.18-8.92 lm) width, polar capsules with 7.4 ± 0.16 lm (6.67-7.56 lm) length and 2.6 ± 0.08 lm (2.52-2.68 lm) width, and morphologically smaller than H. caudalongula, parasitizing Prochilodus lineatus, described by Adriano et al (2005), with spores averaging 71 ± 1.4 lm total length, body measuring 16.6 ± 0.5 lm length and 6.5 lm (6-7 lm) width, polar capsules with 6.1 ± 0.2 lm length and 1.6 ± 0.2 lm width, presenting a length of tail proportion approximating that of the tail length for H. nagelii described by de Azevedo et al (2013), with 22.4 ± 4.0 lm (14.7-27.3 lm), although when compared with the length of the body, it was proportional (Table 1). Lom and Arthur (1989), emphasize that the classification and identification of myxosporids are based on morphological characteristics that are specific to each spore, as well as the modes of infection, which in each environment, present specificity in both the host and the tissue infected, thus complicating morphological similarity.…”
Section: Discussionmentioning
confidence: 51%
“…The spore for this study was shown to be larger in relation to those described in Velasco et al (2016) who identified H. paraensis, parasitizing Cichla temensis in the Tocantins river, state of Pará with spores averaging 42.3 ± 0.65 lm of total length, with body measuring 12.8 ± 0.42 lm (12.38-13.22 lm) in length and 8.6 ± 0.32 lm (8.18-8.92 lm) width, polar capsules with 7.4 ± 0.16 lm (6.67-7.56 lm) length and 2.6 ± 0.08 lm (2.52-2.68 lm) width, and morphologically smaller than H. caudalongula, parasitizing Prochilodus lineatus, described by Adriano et al (2005), with spores averaging 71 ± 1.4 lm total length, body measuring 16.6 ± 0.5 lm length and 6.5 lm (6-7 lm) width, polar capsules with 6.1 ± 0.2 lm length and 1.6 ± 0.2 lm width, presenting a length of tail proportion approximating that of the tail length for H. nagelii described by de Azevedo et al (2013), with 22.4 ± 4.0 lm (14.7-27.3 lm), although when compared with the length of the body, it was proportional (Table 1). Lom and Arthur (1989), emphasize that the classification and identification of myxosporids are based on morphological characteristics that are specific to each spore, as well as the modes of infection, which in each environment, present specificity in both the host and the tissue infected, thus complicating morphological similarity.…”
Section: Discussionmentioning
confidence: 51%
“…Owing to their negative impact on fish, myxosporeans have attracted much attention (Lom and Dyková 2006, Liu et al 2010a, Fiala et al 2015, Velasco et al 2016. To date, approximately 2,300 myxosporean species have been described based on spore morphology (Fiala et al 2015).…”
mentioning
confidence: 99%
“…In China, several morphologically similar myxosporean species infecting different tissues and organs of different hosts were misidentified as the same species (Chen and Ma 1998). Therefore, it is crucial to validate the already described myxosporean species and identify cryptic and new myxosporean species by combination of spore morphology, biological traits (host species/family specificity, organ specificity, tissue tropism), and molecular data (Liu et al 2014a, Thabet et al 2016, Velasco et al 2016.…”
mentioning
confidence: 99%
“…Myxozoans are microscopic metazoan parasites of the phylum Cnidaria (Jiménez-Guri et al, 2007) which parasitise many fish species of economic interest, and may also infect other vertebrates, such as birds, amphibians, reptiles, and mammals (Lom & Dyková, 2006;Bartholomew et al, 2008;Bartošová et al, 2013;Aguiar et al, 2017;Matos et al, 2018). These parasites can spoil the produce of fish farms by rendering the meat unfit for human consumption (Naldoni et al, 2009;Feist & Longshaw, 2006;Velasco et al, 2016). Myxozoans parasitise fish as myxospores, which may present a variety of shapes and sizes, with one or more amoebic sporoplasms, and typically two, but sometimes more polar capsules (Pavanelli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%